Ganoderma lucidum polysaccharide reduces melanogenesis by inhibiting the paracrine effects of keratinocytes and fibroblasts via IL‐6/STAT3/FGF2 pathway. Issue 12 (21st May 2019) - Jiang, Ling; Huang, Jinhua; Lu, Jianyun; Hu, Shuanghai; Pei, Shiyao; Ouyang, Yujie; Ding, Yufang; Hu, Yibo; Kang, Liyang; Huang, Lihua; Xiang, Hong; Zeng, Qing; et al.
Abstract: Our previous study found that Ganoderma lucidum polysaccharide (GLP), bioactive ingredients from Ganoderma lucidum, protected fibroblasts from photoaging. However, whether GLP can affect melanogenesis in melanocytes through regulating paracrine mediators that secreted by keratinocytes and fibroblasts is unclear. We aimed to investigate the efficacy and mechanisms of action of GLP in melanogenesis by regulating paracrine effects of keratinocytes and fibroblasts. The effect of GLP on cell viability affected by GLP was measured by the 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide (MTT) assay. After an immortal keratinocyte line (HaCaT) and primary fibroblasts (FB) were treated with GLP, the supernatants of HaCaT and FB cells were collected and cocultured with an immortalized melanocyte line (PIG1). The expression levels of melanogenesis‐associated genes in PIG1 cells were measured by quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot analysis. Furthermore, FRS‐2, ERK, JNK, and p38 phosphorylation levels were measured. Then, major melanogenic paracrine mediators in HaCaT and FB cells treated with GLP were evaluated by qRT‐PCR and enzyme‐linked immunosorbent assay (ELISA). In addition, the expression of IL‐6 and STAT3 was examined in HaCaT and FB cells. GLP was not cytotoxic to HaCaT and FB cells. The supernatants of GLP‐treated HaCaT and FB cells downregulated the expression levels of MITF, TYR, TYRP1, TYRP2, RAB27A, and FSCN1 genes and inhibited the phosphorylation of FRS‐2, ERK, JNK, and p38 in PIG1 cells. GLP also decreased FGF2 secretion in HaCaT and FB cells. Moreover, GLP reduced IL‐6 expression and STAT3 phosphorylation in HaCaT and FB cells. GLP reduced melanogenesis in melanocytes by inhibiting the paracrine effects of keratinocytes and fibroblasts via IL‐6/STAT3/FGF2 pathway. Abstract : Ganoderma lucidum polysaccharide (GLP) inhibited FGF2 secretion by inactivating the IL‐6/STAT3 pathway in keratinocytes and fibroblasts; consequently, this restrained the phosphorylation of FRS‐2, and inactivated the MAPK pathway in melanocytes, thereby reducing melanogenesis. This finding suggests that GLP may be a feasible agent to prevent pigmentation due to its skin‐whitening effect.